Time relationship between metamorphism and deformation in proterozoic rocks of the Lunavada region, Southern Aravalli Mountain Belt (India): a microstructural study - Mamtani, Manish A.; Merh, Sukumar S.; Karanth, R. V.; Greiling, Reinhard O. (Journal of Asian earth sciences, 2001)
The southern margin of the Aravalli Mountain Belt (AMB) is known to have undergone polyphase deformation during the Mesoproterozoic. The Lunavada Group of rocks, which is an important constituent of the southern parts of AMB, reveals three episodes of deformation; D1, D2 and D3. In this paper, interpretations based on petrographic studies of schists and quartzites of the region are presented and the relationship between metamorphic and deformational events is discussed. It is established that from north to south, there is a marked zonation from chlorite to garnet-biotite schists. Metamorphism (M1) accompanied D1 and was progressive. M2-1 metamorphism associated with major part of D2 was also progressive. However, M2-2 that synchronized with the waning phases of D2 and early-D3 deformation was retrogressive. Porphyroblast-matrix relationships in the garnet-biotite schists of the region have been useful in establishing these facts. The metamorphic rocks studied were intruded by Godhra Granite during the late-D3/post-D3 event. The heat supplied by this granite resulted in static recrystallization and formation of annealing microstructures in rocks close to the granite. It is established that Grain Boundary Migration Recrystallization associated with dislocation creep and Grain Boundary Area Reduction were the two deformation mechanisms dominant in rocks lying far and close from the Godhra Granite, respectively.
Available online 27 November 2000
Gesehen am 22.09.2020